KUALITAS PELAYANAN PEMBUATAN NOMOR POKOK WAJIB PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA MANADO - Manossoh, Anastasia Devita; Tulusan, Femmy; Londa, Very Yohanis (Sam Ratulangi University, 2018)
ABSTRAK: In order to pay part of the people's wealth for the state, the question that often arises in the societyis how the procedure of payment and supervision implementation, so that was born Law Republic of IndonesiaNumber 6 Year 1983 About General Provisions and Procedures Taxation and has been revised and changedinto Law of the Republic of Indonesia Number 28 Year 2007. It is realized that there are still things that havenot been accommodated so as to demand the need for improvement in line with socio-economic developmentand government policy. In addition, public expectations of the existence of increasingly capable and clean taxlaws remain to be considered in various provisions. As with one of the government organizations, theorganization in the Tax Office Pratama Manado City also requires a strong commitment and serious to be ableto run a variety of services covering the field of taxation, one of the services making Taxpayer IdentificationNumber (NPWP). Tax Office Pratama Manado city is also inseparable from the complicated problems, as seenwhen pre-survey conducted found some problems that still complicate the Tax Office Pratama Manado inproviding services Taxpayer Identification Number (NPWP).Kata kunci: Kualitas Pelayanan, Pembuatan, Wajib Pajak